Lagerstroemia yangchunensis (Lythraceae), a new species from Guangdong, China - Bao-Huan Wu; Xiu-Ting Liu; Zi-Yu Bao; Xiao-Yan Ma; Ying Chen; Guo-Di Chen; Xing Hu; Guo-Feng Liu; Se-Ping Dai (PhytoKeys)
A new species from southern China, Lagerstroemia yangchunensis B.H.Wu & G.D.Chen, sp. nov., is described in the present paper. This species is morphologically similar to L. duperreana Pierre ex Gagnep., but can be distinguished by its coarse bark with vertical fissures, calyx lobes glabrous inside, and flowers with shorter pseudopedicels and petals with longer claws. Detailed morphological characteristics, habitat information, and comparisons with similar species are provided.